Denda Adat pada Tradisi Pepadun Masyarakat Lampung dalam Perspektif Hukum Islam - Tri Wahyuni; Inni Inayati Istiana; Ratna Asmarani (Balai Penelitian dan Pengembangan Agama Semarang, 2023)
The people of Lampung, who are predominantly moslem, have a form of implementing customary fines known as dau. There is the term cepala or cepalau, which means 'violation of customary law' in Lampung, which is generally based on Islamic law. The people of Lampung, especially the Pepadun custom in West Tulangbawang Regency, adhere to customary law, which is a reflection of self-esteem that is relevant to the culture of the archipelago. This article aims to find out the practice of